All-trans retinoic acid plus high-dose dexamethasone as first-line treatment for patients with newly diagnosed immune thrombocytopenia: a multicentre, open-label, randomised, controlled, phase 2 trial. Issue 10 (October 2021) - Huang, Qiu-Sha; Liu, Yi; Wang, Jing-Bo; Peng, Jun; Hou, Ming; Liu, Hui; Feng, Ru; Wang, Jing-Wen; Xu, Lan-Ping; Wang, Yang; Huang, Xiao-Jun; Zhang, Xiao-Hui
Summary: Background: High-dose dexamethasone is the standard initial treatment for patients with immune thrombocytopenia, but many patients still relapse and require further treatments. All-trans retinoic acid has been shown to exert immunomodulatory effects and promote thrombopoiesis, and so we aimed to assess the activity and safety of all-trans retinoic acid plus high-dose dexamethasone as a first-line treatment for newly diagnosed patients with immune thrombocytopenia. Methods: This multicentre, open-label, randomised, controlled, phase 2 trial was done at six different tertiary medical centres in China. Eligible participants were adults (aged >18 years) with treatment-naive, newly diagnosed, primary immune thrombocytopenia who had either a platelet count of less than 30 × 10 9 platelets per L or a platelet count of less than 50 × 10 9 platelets per L and clinically significant bleeding. We randomly assigned (1:1) participants to receive either all-trans retinoic acid (10 mg orally twice daily for 12 weeks) plus high-dose dexamethasone (40 mg/day intravenously for 4 consecutive days) or high-dose dexamethasone alone using a central, web-based randomisation system. If patients did not respond by day 14, the 4-day course of dexamethasone was repeated. The primary endpoint was 6-month sustained response, defined as the maintenance of a platelet count of at least 30 × 10 9 platelets per L and at least 2-times higher than the baseline count and the absence of bleeding, with no need for rescue medication at this time. The primary endpoint was analysed by intention-to-treat and safety was assessed in all participants who received at least one dose of the study drug. This trial is registered with ClinicalTrials.gov, NCT04217148, and is now completed. Findings: Between Jan 1, 2020, and June 30, 2020, 132 patients were randomly assigned to either all-trans retinoic acid plus high-dose dexamethasone (n=66) or high-dose dexamethasone alone (n=66). Three patients did not receive their allocated treatment, leaving 129 in the safety analysis set. At 6 months, a significantly higher proportion of participants in the all-trans retinoic acid plus high-dose dexamethasone group (45 [68%] of 66) than in the high-dose dexamethasone monotherapy group (27 [41%] of 66) had a sustained response (OR 3·095, 95% CI 1·516–6·318; p=0·0017). The most common adverse events were dry skin (31 [48%] of 64 patients), headaches (12 [19%]), and insomnia (12 [19%]) in the combination group, and insomnia (ten [15%] of 65 patients) and anxiety or mood disorders (eight [12%]) in the monotherapy group. Both treatments were well tolerated and no grade 4 or worse adverse events occurred. There were no treatment-related deaths. Interpretation: The combination of all-trans retinoic acid and high-dose dexamethasone was safe and active in newly diagnosed patients with primary immune thrombocytopenia, providing a sustained response. This regimen represents a potential first-line treatment in this setting, but further studies are needed to validate its efficacy and safety. Funding: The Beijing Municipal Science and Technology Commission, the National Natural Science Foundation of China, the Beijing Natural Science Foundation, the National Key Research and Development Program of China, and the Foundation for Innovative Research Groups of the National Natural Science Foundation of China.